The Challenges of Muslim Countries in Business World - Rafidah Binti Haji Amidon Amal Norhaizah (Universitas Muhammadiyah Malang, 2017)
Throughout the centuries, the Muslim countries has evolved and branched out to the world of arts, literature, philosophy, technology, economy, law and ethics, education, even politics inclusive of its conflict. Most of what occurred throughout the centuries was documented and used as reference in future studies such as studied done in medical by Ibnu Sina. Many part of the world have form negative perspectives of the Muslim countries especially by correlating negative incidents occurred in some part of the world as practice of all Muslim in the Muslim countries. Living in the Muslim countries has its advantages and disadvantages in which it will be discussed further in this essay. from the discussion below, it can be conclude that any world no matter the religion, the belief, the political standing is bombarded with dilemmas of identifying the advantages and disadvantages of their world to face the challenges of globalization. Distinguishing the advantages or the disadvantages without implicating neither sense of pride or sense of shame has been the practice that is being encouraged by all. The most important impression that the Muslim world can make is through the beauty of tolerance, understanding and the concept of sharing without judging others.